Aging and evolutionary medicine - Partridge, Linda (Henry Stewart Talks, 2007)
Declined mortality in industrialized societies, Maximum human longevity, Werner's syndrome, Common age-related pathologies, The force of natural selection declines with age, Mutationaccumulation theory, The pleiotropy or trade-off theory, Evolutionary theories of aging, Aging in different organisms, Testing the theories, Interventions that slow aging in diverse organisms, Insulin/IGF-like signaling, Genetic effects on lifespan, Extension of lifespan by dietary restriction
Reviewed at 2021/06/12